Social web metrics - González-Fernández-Villavicencio, Nieves (Anuario ThinkEPI, 2013)
Libraries have been using social media for a long time to meet specific goals, however it is essential to use metrics to know the success or failure reached. The goals that business and libraries pursue in any social media plan are the same: increase confidence in the brand (reputation), achieve user/customer satisfaction (engagement), increase sales (increased use of the library and user collaboration) and ultimately reduce costs. But when we have to measure these goals is not enough to measure the ROI (return on investment), and other metrics are necessary, such as the IOR, impact on relationships, or ROC, return on collaboration. Definitely we must focus on the perceived value by the users, in terms of their investment in the library of their time, energy and confidence. We present a proposal of measurement based on four objectives, which address both the metrics for each goal and the most appropriate measurement tools.
Keywords: ROI; Metrics; Social web; Measurement tools; Value of libraries.